Analisis Pendekatan Kecurangan Pelaporan Keuangan Menggunakan Model Fraud Diamond - Bahrul; Nunung Nuryani; Zaenal Arifin (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
Financial statement fraud is a high incidence of fraud compared to corruption and misuse of assets. The purpose of this study is to determine how financial stability, nature of industry, change in auditor, change of directors and financial statement fraud, in construction companies listed on the Indonesia stock exchange in 2019 2023. The data source used in the study is data obtained from the annual financial statements of construction companies listed on the Indonesia Stock Exchange in 2019-2023. The study used 85 sample data from 17 companies for 5 years of research. Sampling using non-probability sampling with purposive sampling technique. To measure the effect of the sample, the classic assumption test analysis, panel data regression analysis and the coefficient of determination and hypothesis testing using common effect model. The results showed that financial stability, nature of industry, change in auditor, change of directors and financial statement fraud can explain financial statement fraud. The results of each variable show that only the nature of the industry has a significant effect on financial statement fraud, while financial stability, change in auditor and change of directors have no significant effect on financial statement fraud.